2007
DOI: 10.5650/jos.56.103
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide Content of Commercial Frying Oil

Abstract: After Swedish researchers reported that heated foods such as potato chips and French fries contain acrylamide, the potential for health damage resulting from the consumption of these foods became a widespread concern. Used frying oils collected from food manufacturing companies were subjected to acrylamide determination using GC/MS-SIM, but the compound was not detected. Thus, we conclude that frying oil used in deep frying would not contaminate foodstuffs with acrylamide and that the recovered oil, much of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Leung et al 23) tested food samples for acrylamide by an LC-MS method and found high levels in all kinds of crisps. But we did not detect it in used frying oil 24) . Velasco et al 25) investigated the formation of monoepoxy fatty acids arising from oleic and linoleic acids in olive oil and sunflower oil.…”
Section: Discussionmentioning
confidence: 98%
“…Leung et al 23) tested food samples for acrylamide by an LC-MS method and found high levels in all kinds of crisps. But we did not detect it in used frying oil 24) . Velasco et al 25) investigated the formation of monoepoxy fatty acids arising from oleic and linoleic acids in olive oil and sunflower oil.…”
Section: Discussionmentioning
confidence: 98%
“…The Japanese ministries of Agriculture, Forestry and Fisheries and of Health, Labour and Welfare published acrylamide values for more than 120 food items (14-16). In addition, all other available data from published articles on acrylamide concentrations in Japanese foods were included (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and the average of all reported values was allotted to individual foods and dishes considering cooking methods and food preparation techniques. For fried vegetables, data for 15 individual vegetables and their products were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, acrylamide can also be formed from frying oil but, in agreement with previous research, this contribution has not been considered. 42 Changes in the antioxidant capacity with the frying time and temperature were also evaluated by direct measurements of the breadcrumbs ( Fig. 5 and 6).…”
Section: Kinetic Experiments: Effect Of Frying Time and Temperaturementioning
confidence: 99%